Sirt1 regulates canonical TGF-β signalling to control fibroblast activation and tissue fibrosis. Issue 1 (1st September 2014) - Zerr, Pawel; Palumbo-Zerr, Katrin; Huang, Jingang; Tomcik, Michal; Sumova, Barbora; Distler, Oliver; Schett, Georg; Distler, Jörg H W
Abstract : Background: Sirt1 is a member of the sirtuin family of proteins . Sirt1 is a class III histone deacetylase with important regulatory roles in transcription, cellular differentiation, proliferation and metabolism. As aberrant epigenetic modifications have been linked to the pathogenesis of systemic sclerosis (SSc), we aimed to investigate the role of Sirt1 in fibroblast activation. Methods: Sirt1 expression was analysed by real-time PCR, western blot and immunohistochemistry. Sirt1 signalling was modulated with the Sirt1 agonist resveratrol and by fibroblast-specific knockout. The role of Sirt1 was evaluated in bleomycin-induced skin fibrosis and in mice overexpressing a constitutively active transforming growth factor-β (TGF-β) receptor I (TBRIact). Results: The expression of Sirt1 was decreased in patients with SSc and in experimental fibrosis in a TGF-β-dependent manner. Activation of Sirt1 potentiated the profibrotic effects of TGF-β with increased Smad reporter activity, elevated transcription of TGF-β target genes and enhanced release of collagen. In contrast, knockdown of Sirt1 inhibited TGF-β/SMAD signalling and reduced release of collagen in fibroblasts. Consistently, mice with fibroblast-specific knockdown of Sirt1 were less susceptible to bleomycin- or TBRIact-induced fibrosis. Conclusions: We identified Sirt1 as a crucial regulator of TGF-β/Smad signalling in SSc. Although Sirt1 is downregulated, this decrease is not sufficient to counterbalance the excessive activation of TGF-β signalling in SSc. However, augmentation of this endogenous regulatory mechanism, for example, by knockdown of Sirt1, can effectively inhibit TGF-β signalling and exerts potent antifibrotic effects. Sirt1 may thus be a key regulator of fibroblast activation in SSc.